2020
DOI: 10.4018/978-1-5225-9452-9.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Health Implications of Plastic Pollution

Abstract: Plastic pollution is one of the prime and alarming issues in developing countries that has vast environmental and human health impacts which need to be addressed as a priority. Unfortunately, limited work has been done on the topic, especially on air and water pollution due to plastics in Pakistan. Informal solid waste management is being done by municipalities, which is not adequate, and the problem will increase with the upsurge in population and industrialization. There is a need to address the knowledge ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Plastic pollution is a primary environmental and health concern in developing countries that must be addressed immediately . Municipal authorities manage solid waste informally, which is insufficient, and the issue will worsen as population and industrialization increase . The cost-benefit analysis showed that producing bioplastic instead of conventional plastic bottles would reduce environmental impacts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plastic pollution is a primary environmental and health concern in developing countries that must be addressed immediately . Municipal authorities manage solid waste informally, which is insufficient, and the issue will worsen as population and industrialization increase . The cost-benefit analysis showed that producing bioplastic instead of conventional plastic bottles would reduce environmental impacts.…”
Section: Introductionmentioning
confidence: 99%
“…14 Municipal authorities manage solid waste informally, which is insufficient, and the issue will worsen as population and industrialization increase. 15 The cost-benefit analysis showed that producing bioplastic instead of conventional plastic bottles would reduce environmental impacts. It is not financially profitable for industrialists to switch.…”
Section: ■ Introductionmentioning
confidence: 99%